Sex Differences in Autism Spectrum Disorder: An Investigation on Core Symptoms and Psychiatric Comorbidity in Preschoolers - Prosperi, Margherita; Turi, Marco; Guerrera, Silvia; Napoli, Eleonora; Tancredi, Raffaella; Igliozzi, Roberta; Apicella, Fabio; Valeri, Giovanni; Lattarulo, Caterina; Gemma, Andrea; Santocchi, Elisa; Calderoni, Sara; et al. (Frontiers in Integrative Neuroscience, 2021)
Findings regarding sex differences in Autism Spectrum Disorder (ASD) as far as core symptoms and psychiatric comorbidities (PC) are inconsistent, inconclusive, or conflicting among studies. The lower prevalence of ASD in females than in males and the age and intelligence quotient (IQ) heterogeneity among samples made it difficult to investigate these differences. This case-control study tries to deepen the impact of sex differences on core symptoms of autism and PC in 214 preschoolers with ASD (mean age 45.26) without impairment in non-verbal IQ (nvIQ≥ 70). 107 ASD females (mean age 44.51 +/- 13.79 months) were matched one-by-one with 107 males (mean age 46.01 +/- 13.42 months) for chronological age (+/- 6 months) and nvIQ (+/- 6 points). We used the Autism Diagnostic Observation Schedule 2 (ADOS-2) and the Child Behavior Checklist (CBCL) 1.5-5 to explore autism severity and PC. The results highlight that ASD females did not significantly differ from ASD males regarding the severity of autism. Statistically significant lower levels of Emotionally Reactive (p=0.005, η2=0.04), Anxious-Depressed (p=0.001, η2=0.05), Internalizing Problems (p=0.04, η2=0.02) and DSM-Oriented Scales (DOS) Anxiety Problems (p=0.02, η2=0.04) in ASD females than in ASD males were also detected. Our findings of no difference in the autism severity and lower internalizing problems in females than males with ASD extend knowledge of autism in females during preschool years. Compared to other similar studies on this topic, we can state that these results are not supported by differences in nvIQ between sexes nor by the presence of cognitive impairment. It confirms the need for clinicians to consider sex differences when describing autism psychopathology.